2020
DOI: 10.20411/pai.v5i1.392
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Clinical and Laboratory Response to Interleukin-6 Receptor Blockade With Tocilizumab in 89 Hospitalized Patients With COVID-19 Pneumonia

Abstract: Background: Pandemic COVID-19 pneumonia due to SARS-2 is an important cause of morbidity and mortality. Emerging evidence links poor outcomes to an inflammatory cytokine storm.Methods: We treated 89 hospitalized patients with COVID-19 pneumonia and heightened systemic inflammation (elevated serum C reactive protein and interleukin-6 levels) with an infusion of tocilizumab (TCZ), a human monoclonal IgG1 antibody to the interleukin-6 receptor.Results: Clinical and laboratory evidence of improvement was evident w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 17 publications
1
9
0
2
Order By: Relevance
“…CRP levels were shown to reduce in 11 patients after TCZ administration (66) . Similar results showed improvement of respiratory status in patients with severe COVID-19 after administration of TCZ [67] , [68] , [69] , [70] , [71] .…”
Section: Inhibition Of Il-6 In Covid-19supporting
confidence: 74%
“…CRP levels were shown to reduce in 11 patients after TCZ administration (66) . Similar results showed improvement of respiratory status in patients with severe COVID-19 after administration of TCZ [67] , [68] , [69] , [70] , [71] .…”
Section: Inhibition Of Il-6 In Covid-19supporting
confidence: 74%
“…The included patients had high inflammatory markers such as ferritin and CRP levels indicating the role of inflammatory markers in the pathophysiology of hypoxia [ 2 , 26 , 28 30 ]. Our patients had significant increase in the CRP at the initiation of therapy indicating a severe disease [ 31 ]. Following therapy, we observed reduction on the CRP on days 7 and 14.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly in a randomized clinical trial of TCZ, there was a reduction in CRP over time in the TCZ arm [ 32 ]. Another study showed that CRP levels decreased from 95 to 14 mg/L ( p < 0.001) [ 31 ]. We had not seen a significant change in lymphocyte count overtime.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…По данным исследований, выполненных в ГБУЗ «ГКБ № 52 ДЗМ», применение тоцилизумаба приводило к быстрому снижению уровня С-реактивного белка и фибриногена -основных доступных в широкой практике биомаркеров, свидетельствующих о выраженности «цитокинового шторма», повышению уровня лимфоцитов и снижению тяжести течения заболевания (снижение оценки по шкале NEWS2 с 5 до 2 баллов) [3,4].…”
Section: For Citationunclassified